Upgrading Kehumasan dengan Pendekatan Komunikasi Interpersonal - Dartina, Vina (Ma'soem University, 2024)
Perumda Tirta Rangga Subang plays a crucial role in providing clean water to the residents of Subang Regency. As the demand for clean water continues to grow, the company must consistently improve its services, both in technical and non-technical aspects. Interpersonal communication is a key element in establishing good relationships between the company and its internal and external public. This community service activity aims to enhance the public relations skills of Perumda Tirta Rangga Subang's employees, with a focus on interpersonal communication, which is expected to improve communication effectiveness and employee professionalism. This activity uses the Participatory Action Research (PAR) method, which involves as many as 122 participants, including employees and management of Perumda Tirta Rangga Subang. The results of this community service activity indicate an improvement in the interpersonal communication skills of Perumda Tirta Rangga Subang's employees, positively impacting service quality, public relations, and conflict management effectiveness. Additionally, this activity has also led to increased employee professionalism, confidence, and work efficiency, contributing to the achievement of the organization's goals. Other positive outcomes include enhanced company reputation and customer satisfaction.